Freilandbeobachtungen an Isotoma viridis Bourlet (Collembola: Isotomidae). - Kühlmann, Dietrich (Contributions to Entomology = Beiträge zur Entomologie, 1958)
On the ice covering a pool near Lipsia in February and March there was noticed Isotoma viridis Bourlet. When there was made a hole into the ice the insects moved there assembling on or in the water. The water being about 7 degrees warmer than air temperature this fact has probably given rise to this motion.